A Way Forward for Assisting Women and Girls in Northern Uganda - Mazurana, Dyan; Carlson, Khristopher; Blattman, Chris; Annan, Jeannie (Tufts Archival Research Center, 2005)
Little is known about the short and long term effects of war on youth. Yet without an understanding of who is at risk of violence (and from whom), the factors that affect violence and acceptance, a sense of the long-term impacts of war violence, and a strong grasp of the factors that protect youth, how can we design more effective prevention, protection, rehabilitation and reintegration programs?